Feasibility and acceptability of a multiple risk factor intervention: The Step Up randomized pilot trial - Richards Julie; Ludman Evette J; Catz Sheryl L; McClure Jennifer B; Riggs Karin; Grothaus Lou (BMC, 2011)
Abstract Background Interventions are needed which can successfully modify more than one disease risk factor at a time, but much remains to be learned about the acceptability, feasibility, and effectiveness of multiple risk factor (MRF) interventions. To address these issues and inform future intervention development, we conducted a randomized pilot trial (n = 52). This study was designed to assess the feasibility and acceptability of the Step Up program, a MRF cognitive-behavioral program designed to improve participants' mental and physical well-being by reducing depressive symptoms, promoting smoking cessation, and increasing physical activity. Methods Participants were recruited from a large health care organization and randomized to receive usual care treatment for depression, smoking, and physical activity promotion or the phone-based Step Up counseling program plus usual care. Participants were assessed at baseline, three and six months. Results The intervention was acceptable to participants and feasible to offer within a healthcare system. The pilot also offered important insights into the optimal design of a MRF program. While not powered to detect clinically significant outcomes, changes in target behaviors indicated positive trends at six month follow-up and statistically significant improvement was also observed for depression. Significantly more experimental participants reported a clinically significant improvement (50% reduction) in their baseline depression score at four months (54% vs. 26%, OR = 3.35, 95% CI [1.01- 12.10], p = 0.05) and 6 months (52% vs. 13%, OR = 7.27, 95% CI [1.85 - 37.30], p = 0.004) Conclusions Overall, results suggest the Step Up program warrants additional research, although some program enhancements may be beneficial. Key lessons learned from this research are shared to promote the understanding of others working in this field. Trial registration The trial is registered with ClinicalTrials.gov (NCT00644995).